The Synagogues of Kentucky : Architecture and History - Weissbach, Lee Shai, 1947- (Book collections on Project MUSE., 1995)
Lee Shai Weissbach's innovative study sheds light on the functioning of smaller Jewish communities in a state representative of many in the Midwest and South. The synagogue buildings of Kentucky tell much about the experience of Kentucky Jewry. Synagogues, especially in smaller towns, have often served as the only setting available for a wide variety of communal activities. Weissbach outlines the history of every congregation established in Kentucky and every house of worship that has served Kentucky Jewry over the last 150 years, considering such issues as the financing of construction, the s.